The site and receptors responsible for the inhibition by sympathetic nerves of intestinal smooth muscle and its parasympathetic motor nerves - Gillespie, J. S. (1977)
1. The effects of three inhibitory stimuli, sympathetic nerve stimulation, noradrenaline (NA) and isoprenaline have been examined on three forms of motor activity in the rabbit colon, the response to pelvic (parasympathetic) nerve stimulation, acetylcholine (ACh) and spontaneous tone. 2. The response to pelvic nerve stimulation is most effectively inhibited by sympathetic nerve stimulation, much less effectively by NA and hardly at all by isoprenaline. The sympathetic nerves can inhibit the pelvic response at frequencies of stimulation which do not affect spontaneous tone. The inhibitory effect of sympathetic stimulation, and of NA, on the pelvic response is reduced by phentolamine 5 × 10(-6) M and unaffected by propranolol 5 × 10(-6) M suggesting the effect is mediated via α receptors. 3. The response to ACh is inhibited by all three stimuli equally. The inhibitory effect of sympathetic nerve stimulation and of isoprenaline is reduced by propranolol 5 × 10(-6) M. The inhibitory effect of NA is also reduced by propranolol but to a lesser extent. Phentolamine 5 × 10(-6) M has a small effect in reducing the inhibitory effect of sympathetic nerve stimulation or of NA. This effect of phentolamine is lost if the participation of motor nerves in the response to ACh is excluded by either tetrodotoxin 10(-7) g/ml. or cold storage for 10-14 days. These results suggest that inhibition of the ACh response takes place mainly at the muscle by activation of β receptors but that ACh may have a small indirect stimulant action through motor nerves and this is susceptible to inhibition through α receptors. 4. All three stimuli are equally effective in lowering smooth muscle tone. This inhibitory effect of sympathetic nerve stimulation and of isoprenaline is reduced by propranolol 5 × 10(-6) M and unaffected by phentolamine 5 × 10(-6) M. The inhibitory effect of NA is reduced by propranolol but again is less sensitive to block than the other two inhibitory stimuli. Phentolamine is without effect on the inhibitory action of NA and the combination of phentolamine with propranolol is no more effective than propranolol alone. These results suggest that NA liberated by sympathetic nerves and isoprenaline inhibit myogenic tone in the smooth muscle by an action on β receptors but the action of NA added to the bath cannot be fully explained in this way.